Winter Street, November 22, 1913 - Unknown (Tufts Archival Research Center, 2005)
Elevated view east-southeast from Tremont Street of Winter Street, located between Washington Street to the east-southeast and Tremont Street to the west-northwest. Signage and awnings adorn the facades of the buildings which line both the north-northeast and south-southwest sides of the street. Pedestrians fill Winter Street. 6 1/8 x 8 7/16, 6 7/16 x 8 7/16 overall Photographs